Rethinking the Penology of Imprisonment: The Case of Palestinian Security Prisoners in Israel - Erez, Edna (The prison journal, 2025)
This article examines the considerations involved in the confinement conditions of Palestinian security violators in Israeli prisons. It challenges the suitability of prevailing penological frameworks to explain security prisoners and argues for a counterterrorism approach. The study reviews security prisoners’ rights and privileges, and how the Israeli-Palestinian conflict and global anti-terrorism efforts shape and reshape prison conditions. It highlights contentious debates around “deserved” prison conditions, especially following the October 7 Hamas attack, and subsequent calls for harsher treatment. The article concludes that confinement policies have implications beyond prison walls and are closely intertwined with broader political and security considerations.